2014
DOI: 10.1007/s13659-014-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Carinatines A and B, Lycopodium Alkaloids from Phlegmariurus carinatus

Abstract: Carinatine A (1), a C16N2-type Lycopodium alkaloid possessing a 5/6/6/6 ring system formed by a new C-4/C-12 bond, and carinatine B (2), the first derivative of lycojaponicumin C, along 16 known compounds, were isolated from the whole plant of Phlegmariurus carinatus. Their structures were elucidated based on the spectroscopic data. The two new isolates were no inhibitory activity for the acetylcholinesterase (AChE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Carinatine A (22) with a unique 5/6/6/6 ring system was first identified from P. carinatus, and its absolute configuration remains unassigned. 31 The concomitant isolation of 18 and 22 in the present study, together with their well-matched ECD curves (Figure S19, Supporting Information), established a (7S,12S,15R) absolute configuration for 22.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Carinatine A (22) with a unique 5/6/6/6 ring system was first identified from P. carinatus, and its absolute configuration remains unassigned. 31 The concomitant isolation of 18 and 22 in the present study, together with their well-matched ECD curves (Figure S19, Supporting Information), established a (7S,12S,15R) absolute configuration for 22.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…The 13 C NMR (Table ) and HMQC data showed 16 carbon resonances, of which the one at δ C 149.3 (C-13) could be assigned to a nitrone moiety. A comparison of the 1D NMR data of 18 with those of carinatine A ( 22 ) revealed that 18 was the 8-hydroxy derivative of carinatine A, which was supported by the 2D NMR data of 18 (Figure S17, Supporting Information). Notably, H-14b (δ H 2.38) showed a ddt splitting pattern ( J = 19.0, 6.0, 2.9 Hz), which was consistent with the 1 H– 1 H COSY correlation of H-14b/H 2 -9, implying unusual five-bond couplings between H-14b and H 2 -9.…”
Section: Results and Discussionmentioning
confidence: 59%
“…Their structures are shown below, and their names and the corresponding plant sources are listed in the Table. As it can be seen, alkaloids and serratane‐type triterpenoids are the dominant chemical constituents in the plants of the genus Phlegmariurus .…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…P. carinatus was used as a traditional herbal medicine in China for long time (Liu et al. 2014 ). It has significant curative effect on rheumatoid arthritis, rheumatoid arthritis, muscle and bone pain (Zhang et al.…”
mentioning
confidence: 99%